Safety and efficacy of the NovaCross microcatheter in facilitating crossing of chronic total occlusion coronary lesions: a multicenter, single-arm clinical trial. Issue 7 (November 2020) - Walsh, Simon J.; Dudek, Darius; Bryniarski, Leszek; Nicholson, William; Karmpaliotis, Dimtri; Uretsky, Barry; McEntegart, Margaret; Assali, Abid; Knaapen, Paul; Kornowski, Ran; Spratt, James C.; Goodwin, Mark; et al.
Abstract : Background: The aim of this study was to evaluate the safety and efficacy of the novel NovaCross microcatheter system in patients with ischemic heart disease due to coronary chronic total occlusions (CTO). Methods: A total of 191 subjects between the ages of 25–80 years were recruited in 10 investigational sites. Each subject underwent a percutaneous coronary intervention (PCI) of a CTO lesion using the NovaCross microcatheter, equipped with expandable nitinol scaffolds to enhance guidewire penetration and crossing of the CTO lesion. The primary safety endpoint was procedural major adverse cardiac events [composite of death, myocardial infarction (MI), or urgent target vessel revascularization]. The primary efficacy endpoint was to assess the ability of the NovaCross microcatheter to successfully facilitate the placement of a guidewire beyond a native coronary CTO in the true vessel lumen. After the PCI, subjects remained in hospital until a 12-lead ECG and blood tests for cardiac biomarkers were taken at 3–6 h and 8–16 h post-procedure. Results: No deaths, urgent revascularization, or urgent coronary artery bypass surgery were reported. The reported MI rate according to the protocol definition was 12.3%, and technical success was achieved in 75.3% of the subjects regardless of CTO procedure technique. In 89.2% of the subjects, the NovaCross succeeded in penetrating the proximal CTO cap, and in 25.8% of the subjects, the extendable portion of the NovaCross crossed the full length of the CTO lesion. Conclusions: The NovaCross met both the primary safety endpoint and the primary efficacy endpoint. We, therefore, conclude that the device is well tolerated, effective, and could be easily adopted by interventional cardiologists.